Illustrated orthopedic physical assessment - Evans, Ronald C. (Mosby/Elsevier, 2009)
Used as a definitive assessment resource by orthopedic practitioners and students alike, this text continues to be known and trusted for both its depth of coverage and its accessible, accurate information. The third edition retains practical features such as gamuts, clinical pearls, and cross-reference tables, while adding more than 500 new illustrations, the majority in full color.